Driven from Home; Or, Carl Crawford's Experience - Alger, Horatio, Jr., 1832-1899 (Salt Lake City, UT : Project Gutenberg, 2006)
"Driven from Home; Or, Carl Crawford's Experience" by Horatio Alger, Jr. is a novel written during the late 19th century. It tells the story of a young boy named Carl Crawford, who at the age of sixteen, finds himself estranged from his wealthy home due to conflicts with his stepmother and stepbrother, leading him to embark on a journey of self-discovery and hard work as he seeks to establish his own identity and earn a living. The opening of the book introduces Carl as he sets out on his quest with very little money but a strong sense of determination. Having experienced the oppressive presence of his stepmother and feeling neglected by his father, Carl decides to leave home to find his own way in the world. As he travels, he encounters both friends and adversaries, including a supportive schoolmate named Gilbert, who assists him in navigating social challenges, and he also faces the maliciousness of his stepbrother, Peter. The beginning sets a tone of resilience and hardship as Carl grapples with the struggles of adolescence against the backdrop of family conflict. (This is an automatically generated summary.)
Release date is 2006-01-21
Produced by Charles Keller and David Widger
Keywords: Didactic fiction; Conduct of life -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Runaway teenagers -- Juvenile fiction